Synergy effect between photocatalysis and heterogeneous photo-Fenton catalysis on Ti-doped LaFeO3 perovskite for high efficiency light-assisted water treatment. Issue 5 (5th February 2020) - Garcia-Muñoz, Patricia; Fresno, Fernando; Lefevre, Christophe; Robert, Didier; Keller, Nicolas
Abstract : Synergy effect between photocatalysis and H2 O2 -mediated heterogeneous photo-Fenton catalysis on highly robust Ti-substituted La1− x Ti x FeO3 perovskites led to high performances under UV-A light in water treatment. Abstract : A strategy combining both heterogenized photo-Fenton and photocatalysis advanced oxidation processes for a single dual catalyst is developed simultaneously benefiting from the higher reaction rate of photo-Fenton and the higher mineralization yield of photocatalysis in water treatment, while overcoming the strong drawbacks still limiting their viability as single processes. We prepared via a facile Pechini sol–gel route a highly efficient and stable Ti-substituted LaFeO3 dual catalyst, acting simultaneously as a reusable photo-Fenton solid catalyst and a photocatalyst in water treatment. The partial substitution of La by Ti ions in the crystalline network led to pure heterogeneous surface reactions with an increase in the catalyst robustness by more than two orders of magnitude, indicating the absence of any Fe released and the stability of catalytic performance with test cycles. It further strongly enhanced the reaction rates, due to both increased availability of the photogenerated charge carriers at the surface and the electronic enrichment of surface Fe, and allowed full mineralization of a pollutant to be achieved at circumneutral pH through combined advanced oxidation processes.